Peran guru dalam membentuk kedisiplinan siswa kelas XI IIS dalam memakai seragam di MA Maarif Sukorejo - Safitri, Wiwit Nahdiyah (Maliki Interdisciplinary Journal, 2024)
This research aims to explore the role of teachers in shaping the discipline of class XI IIS students in wearing uniforms at MA Maarif Sukorejo. The research method used is qualitative with a case study approach. Data was collected through classroom observations, interviews with teachers and students, as well as analysis of documentation related to school policies. The research results show that teachers have an important role in forming students’ discipline in complying with uniform rules. Teachers provide active supervision, set an example by adhering to their own uniform rules, and provide a deep understanding of the importance of discipline in building school identity. However, challenges such as variations in interpretation of uniform rules and lack of consistency in rule enforcement were also identified. This research contributes to an understanding of the role of teachers in shaping student discipline in the school environment, as well as providing recommendations for developing policies that are more effective in improving student discipline.